2004
DOI: 10.1007/s10340-003-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Feeding activity and life history characteristics of the generalist predator, Chrysoperla carnea (Neuroptera: Chrysopidae) at different prey densities

Abstract: Larvae of the common green lacewing, Chrysoperla carnea (Stephens) (Neuroptera :Chrysopidae) were fed with different densities of Hyalopterus pruni (Geoffer) (Homoptera: Aphididae) in Petri dishes under laboratory conditions. Functional response, developmental time, mortality rate and fecundity of the predator were measured. Treatments were carried out at 25±1°C, 65±5% RH and a 16L:8D photoperiod in a controlled temperature cabinet. Prey was given at densities of 5, 10, 20, 40, 80, 160 and 250 aphids per larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
41
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 14 publications
13
41
1
3
Order By: Relevance
“…the same as our results. Atlihan et al, (2004) studied that this period on different prey densities of S. cerealella eggs was 6.7±0.58 to 8.2±0.37 (d), Nawaz et al, (2008) recorded that the pre-oviposition period on control artificial diet treatment (Honey, water and yeast ) was 6.08 (d) that is very close to our result. But Sattar et al, (2010) showed different results such as (3.25±0.16 to 4.9±0.14 d) (2.37±018 d) (3.12±0.22 to 3.37±0.18 d) because of different level of protein's concentration in their artificial diet, rearing on S. cerealella eggs, and at 24-32 0 C, respectively.…”
Section: Larval and Pupal Weightssupporting
confidence: 91%
“…the same as our results. Atlihan et al, (2004) studied that this period on different prey densities of S. cerealella eggs was 6.7±0.58 to 8.2±0.37 (d), Nawaz et al, (2008) recorded that the pre-oviposition period on control artificial diet treatment (Honey, water and yeast ) was 6.08 (d) that is very close to our result. But Sattar et al, (2010) showed different results such as (3.25±0.16 to 4.9±0.14 d) (2.37±018 d) (3.12±0.22 to 3.37±0.18 d) because of different level of protein's concentration in their artificial diet, rearing on S. cerealella eggs, and at 24-32 0 C, respectively.…”
Section: Larval and Pupal Weightssupporting
confidence: 91%
“…Although the larval developmental time (from first instar to adult) of the predator at a density of 20 prey/ day was longer than that at densities >20 prey/day, larvae were able to develop to adulthood and complete the life cycle at all prey densities used in this study. Atlıhan et al (2004) reported that a shorter developmental time with higher prey densities was due to the fact that energy needed by the larvae to develop into adults was acquired within a shorter time at higher prey densities. Results reported for some other coccinellids and a generalist predator (Chrysoperla carnea) showed similarity with the results obtained in this study (Kawauchi 1987;Atlıhan 1997;Atlıhan et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Atlıhan et al (2004) reported that a shorter developmental time with higher prey densities was due to the fact that energy needed by the larvae to develop into adults was acquired within a shorter time at higher prey densities. Results reported for some other coccinellids and a generalist predator (Chrysoperla carnea) showed similarity with the results obtained in this study (Kawauchi 1987;Atlıhan 1997;Atlıhan et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) is one of the most important natural enemies in apple orchards (Freitas and Penny, 2001;Medina et al, 2003;Athan et al, 2004) and has been reported as an efficient biological control agent of the San Jose scale Quadraspidiotus perniciosus (Comstock, 1881) (Hemiptera: Diaspididae), the apple aphid Aphis citricola van der Goot, 1912 (Hemiptera: Aphididae), and the European red spider mite Panonychus ulmi (Koch, 1836) (Acari: Tetranychidae) (Ribeiro and Flores, 2002;Bezerra et al, 2006;Giolo et al, 2009), which are important arthropod pests of apple orchards in southern Brazil.…”
mentioning
confidence: 99%